2015
DOI: 10.1039/c5nr00353a
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-dependent Ag+release from silver nanoparticles and its complexation in AgS2sites in primary murine macrophages

Abstract: Silver nanoparticle (AgNP) toxicity is related to their dissolution in biological environments and to the binding of the released Ag(+) ions in cellulo; the chemical environment of recombined Ag(+) ions is responsible for their toxicological outcome, moreover it is indicative of the cellular response to AgNP exposure, and can therefore shed light on the mechanisms governing AgNP toxicity. This study probes the chemistry of Ag species in primary murine macrophages exposed to AgNPs by making use of X-ray Absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 27 publications
(42 reference statements)
6
93
0
Order By: Relevance
“…Using XANES, Ag + ions released from 60 nm AgNPs inside primary murine macrophages were shown to form complexes with thiolate groups, with glutathione identified as the most likely ligand. 22 However, these studies need to be confirmed using AgNWs.…”
Section: Resultsmentioning
confidence: 98%
“…Using XANES, Ag + ions released from 60 nm AgNPs inside primary murine macrophages were shown to form complexes with thiolate groups, with glutathione identified as the most likely ligand. 22 However, these studies need to be confirmed using AgNWs.…”
Section: Resultsmentioning
confidence: 98%
“…From the comparison of the theoretical pI and Mr of the proteins with the observed ones for the spots of interest we can often know if we are dealing with protein fragments or with intact proteins. However, even if we know that we are dealing with intact proteins, we seldom can know if we are dealing with a minor or a major form, with an active or an inactive form [67]. 2D blotting can provide useful information in terms of description of the landscape of protein species, but is not problem-free (antibodies cross-reactivities, maps realignments between 2D blots and stained patterns).…”
Section: Discussionmentioning
confidence: 98%
“…The protein regulating glutathione neosynthesis, GCLM, is also induced by zinc oxide and zinc ion, which is not surprising as glutathione is an important part in the cellular responses to thiophilic metals such as zinc [65], copper [66] and silver [67]. The heme oxygenaseferritin pathway, the biliverdin reductase and the formylglutathione hydrolase also belong to these protective proteins increased in response to zinc oxide, but not necessarily in response to zinc ion.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the Ag(0) to Ag + dissolution and the consequent complexation with biological thiols is the main key to unravel Ag toxicity. Veronesi and coworkers in series of very interesting articles deeply investigated the chemical nature of Ag-S bond and its relationship with cellular environment [62][63][64]. As reported in Figure 5, Ag K-Edge XANES region comparison evidenced a clear qualitative trend consisting in the progressive dumping of the signal as a function of time.…”
Section: Speciation Of Metallic Nanoparticlesmentioning
confidence: 96%